Eculizumab‐related drug reaction in a patient with neuromyelitis optica - Rishi Sharma; Moises Romo; Flavia Nelson (Clinical Case Reports, 2023)
Abstract Eculizumab is approved for treatment of antibody positive neuromyelitis optica, myasthenia gravis, and hematologic disorders like paroxysmal nocturnal hemoglobinuria. Drug rash has not yet been reported as a side effect of eculizumab. We report a case of a cutaneous drug reaction soon after introduction of eculizumab therapy in a patient with refractory neuromyelitis optica. Clinicians should be aware of a drug reaction as a possible adverse reaction to eculizumab.